Quantitative CT Attenuation Cut-off Values for Lesion Characterization: Enostoses in Patients Without Malignancy Versus Osteoblastic Metastases in Breast Cancer - Novita Pitri; Mathelda Diah Wulandari; Dario Agustino Nelwan; Patricia Jorisal; Ivana Dewi Mulyanto; Ratna Sari Wijaya (Medicinus, 2026)
Background: Incidental osteoblastic bone lesions detected on CT scans, such as enostoses and osteoblastic metastases, often pose diagnostic challenges, especially in patients with or without a history of breast cancer. Hounsfield unit (HU) attenuation values have been proposed to differentiate these lesions non-invasively, however, variability in cut-off values exists in prior studies.   Methods: This observational analytic case-control study included adult patients who underwent CT and FDG PET-CT at MRCCC Siloam Semanggi Hospital, Jakarta from 2020 to 2025. Controls were patients with enostoses and no history of malignancy, while cases were breast cancer patients with PET/CT-confirmed osteoblastic metastases. Mean and maximum HU values were measured and analyzed to determine optimal cut-offs.   Result: Mean and maximum HU values were significantly higher in enostoses than in osteoblastic metastases (mean: 1025 ± 123.66 vs. 449.65 ± 106.93; maximum: 1167.77 ± 106.20 vs. 599.34 ± 134.78; p < 0.001). A mean HU cut-off of 692 achieved 100% sensitivity, 98.36% specificity, and an AUC of 0.992. A maximum HU cut-off of 860 showed 79.61% sensitivity, 100% specificity, and an AUC of 0.898.   Conclusions: Mean and maximum HU values on CT are highly effective for differentiating enostoses from osteoblastic metastases in breast cancer patients.